"Adaptación del híbrido de maíz (Zea mays) agri-350 en el cantón Balzar durante la época seca" - Estrada Miguez, Neiser Geovanny (2020)
The evaluation of the Agri-350 hybrid in contrast to the other materials under study, was carried out with the objective of determining its performance and adaptability, with a view to contributing to the increase of maize production in agricultural areas par excellence. The present study took place in the farm "La Carlota", located in the 41st km of the road to Balzar, 1.5 km from the Zapallo stop in the sector of La Guayaquil. The test corresponded to a completely randomized block design (DBCA), consisting of 6 treatments (Agri-350, ADV - 9735, P- 3862, Somma, P - 4039, H - 551) and 4 repetitions. The criterion for the selection of this design is due to the presence of slopes in the place where the experimental plots were established. The data obtained were subjected to an analysis of variance (ANOVA) and separation of means through Tukey's test (p≤ 0.05). The hybrids presented statistical differences in all the variables under study; however, with respect to productive parameters such as: cob coverage, number of grains per cob, number of rows of grains, diameter of cob and yield, the hybrid Agri-350 stood out precisely, managing to demonstrate a high phenotypic plasticity to the agroclimatic conditions of the area. Additionally, the hybrid Agri-350 obtained a profitability of 91.37%, demonstrating a higher net benefit in production, which would indicate a greater feasibility at the time of implementation in commercial lots. Keywords: hybrid, phenotypic plasticity, adaptability, productivity, performance